A quick-assessment procedure to evaluate the degree of conservation of rockfall drapery meshes (Fracture and Structural Integrity, 2018)
Drapery meshes are protection devices installed on a cliff for mitigating rockfall hazard. They can prevent the detachment of rock fragments and control the dynamics of the falling blocks. During their design working life, drapery meshes are subjected to ageing phenomena, corrosion and impact, which can invalidate the purposes of the protection devices. A novel procedure based on a multi-hierarchical assessment of the damages is proposed. The approach is tailored for two technologies well diffused in the Alps. The main components of the system are identified and the effects of each potential damage on the overall behaviour are taken into account through risk analysis approached. A site campaign serving to test the procedure is described. The proposed approach can be modified to consider other drapery mesh installation types.
Keywords: Rockfall; Drapery mesh; quick assessment; ageing effects